Teachers' Barriers in Implementing Merdeka Curriculum in Teaching English at Junior High School: Merdeka Curriculum - Wahyusi Muhtar; Masruddin; Wisran (Universitas Islam Negeri Palopo, 2025)
This study examines the barriers encountered by English teachers in implementing the Merdeka Curriculum at UPT SMPN 1 Sabbang Selatan. The research employs a qualitative descriptive approach, with data collected through observations, interviews, and documentation. The findings reveal that teachers face significant challenges in curriculum comprehension, resource availability, and assessment adaptation. Specifically, teachers struggle with understanding differentiated instruction, utilizing digital tools, and developing student-centered learning strategies. Additionally, limited access to teaching resources and inadequate training hinders effective curriculum execution. Classroom observations indicate that while some teachers attempt to implement innovative strategies, traditional methods remain dominant due to insufficient support. Assessment practices also vary, with some teachers effectively using structured rubrics, while others lack proper evaluation techniques. The study concludes that addressing these barriers requires targeted professional development programs, enhanced resource allocation, and institutional support to improve curriculum implementation. Future research should explore intervention strategies to overcome these barriers and optimize English language teaching under the Merdeka Curriculum framework.